Alpha casozepine and L-theanine in ameliorating stress levels in infertile couples: a review - Ahire, Prachi; C., Stalin; Saha, Suman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Globally, the fertility rate has decreased significantly in the last two decades. Infertility can lead to psychological and emotional stress, particularly for couples who have been married for a long period. According to the literature, stress can alter the metabolic environment and reduce the likelihood of pregnancy. The fertility treatments involving assisted reproductive technology put additional physical, mental, and financial strain on patients, especially women who are frequently subjected to invasive procedures as part of the process. Stress affects the hypothalamic-pituitary-adrenal (HPA) axis, the concentration of reproductive hormones (FSH, GnRH, and LH), and other biological processes through a variety of mechanisms. Alteration of glucocorticoid hormone levels in the blood was observed because of stress in infertile couples. Moreover, the males also get affected by stress as per the semen parameters and quality analysis. Available evidence strongly suggests that stress reduction should be the first step in a fertility therapy regimen. Further, managing stress can boost ovarian function and semen parameters. The current review focuses on the state-of-the-art research on stress-induced reproductive dysfunction as well as the positive effects of alpha-casozepine, an anxiolytic-like bioactive decapeptide and L-theanine, an amino acid found primarily in green tea on reducing stress levels and improving treatment outcomes in infertile couples.